Optimization of Synthesis Amounts of Polymers with Two Monomers by Different Methods Based on Response Surface Methodology. Issue 2 (26th November 2013) - Tian, Minglei; Park, Haeun; Row, Kyung Ho
ABSTRACT To synthesize a monolithic polymer with two different monomers, 17‐run Box–Behnken design (BBD) and 20‐run central composite design (CCD) were investigated and optimized three factors (volume of monomer, cross‐link, and porogen). According to the variance of the fitted quadratic polynomial model, BBD was more suitable for the two monomers than CCD. The adjusted coefficient of determination (RAdj2) for the model (0.995 and 0.997 for the two monomers) as well as the probability (p < 0.0001) revealed high significance of the regression model. The following optimized synthesis conditions were suggested by the BBD method (0.54 mL of monomer, 2.93 mL of cross‐link, and 2.95 mL of porogen for methyl methacrylate (MAA); 0.55 mL of monomer, 2.98 mL of cross‐link, and 2.86 mL of porogen for 2‐hydroxyethyl methacrylate (2‐HEMA)). Finally, 5137.6 and 4789.9 mg of MAA and 2‐HEMA monomers were predicted, respectively. © 2013 Wiley Periodicals, Inc. Adv Polym Technol 2014, 33, 21405; View this article online at wileyonlinelibrary.com. DOI 10.1002/adv.21405